Effectiveness of Dialectical Behavioral Therapy on Reduction of Recidivism Among Recently Incarcerated Homeless Women: A Pilot Study - Nyamathi, Adeline (International journal of offender therapy and comparative criminology, 2018)
The purpose of this pilot randomized controlled trial (RCT) was to compare the 6-month outcomes of a Dialectical Behavioral Therapy-Corrections Modified (DBT-CM) program versus a Health Promotion (HP) program on mitigating recidivism among 130 female parolees/probationers between baseline and 6-month follow-up. The effect of DBT-CM on reducing recidivism was greater among those who expressed a desire for help (risk ratio [RR] = 0.40; 95% confidence interval [CI] = [0.16, 1.00]; p = .050) and among homeless female ex-offenders (HFOs) who were younger (<50 years of age; RR = 0.46; 95% CI = [0.19, 1.11]; p = .085) and participants with Desire for Help score > 35 (Model 3; RR = 0.40; 95% CI = [0.16, 1.00]; p = .050). Findings from this pilot study suggest that the DBT-CM intervention may be effective in reducing reincarceration rates among some HFOs during reentry. Larger RCTs are needed to validate our findings.